Programmable DC high voltage power supply (5kV) /cMuhammad Firdhaus Khairil Mokhtar - Muhammad Firdhaus Khairil Mokhtar, 1990-; Abd. Rahman Tamuri; Fakulti Sains (2012)
Project Paper (Sarjana Muda Sains (Fizik Industri)) - Universiti Teknologi Malaysia, 2012